Financial Ombudsman – Analysis of Activities in the field of alternative disputes resolution - Iczetkin, Aleksandra; Hernik, Agata (Journal of Finance and Financial Law, 2019)
Article presents the institution of Financial Ombudsman, who takes actions for benefit of the financial services market’s clients. Author sets out with the aim of presenting complaining procedure and analyzing present activities of Financial Ombudsman and future possible changes in Alternative Dispute Resolution sector.